VTE risk assessment in cancer - Ay, C.; Pabinger, I. (Phlebologie, 2016)
Venous thromboembolism (VTE) in patients with cancer is associated with an increased morbidity and mortality, and its prevention is of major clinical importance. However, the VTE rates in the cancer population vary between 0.5–20 %, depending on cancer-, treatment- and patient-related factors. The most important contributors to VTE risk are the tumour entity, stage and certain anticancer treatments. Cancer surgery represents a strong risk factor for VTE, and medical oncology patients are at increased risk of developing VTE, especially when receiving chemotherapy or immunomodulatory drugs. Also biomarkers have been investigated for their usefulness to predict risk of VTE (e.g. elevated leucocyte and platelet counts, soluble P-selectin, D-dimer, etc.). In order to identify cancer patients at high risk of VTE and to improve risk stratification, risk assessment models have been developed, which contain both clinical parameters and biomarkers. While primary thromboprophylaxis with low-molecular- weight-heparin (LMWH) is recommended postoperatively for a period of up to 4 weeks after major cancer surgery, the evidence is less clear for medical oncology patients. Thromboprophylaxis in hospitalized medical oncology patients is advocated, and is based on results of randomized controlled trials which evaluated the efficacy and safety of LMWH for prevention of VTE in hospitalized medically ill patients. In recent trials the benefit of primary thromboprophylaxis in cancer patients receiving chemotherapy in the ambulatory setting has been investigated. However, at the present stage primary thromboprophylaxis for prevention of VTE in these patients is still a matter of debate and cannot be recommended for all cancer outpatients.
Keywords: Venous thromboembolism; cancer; hypercoagulability; risk factors; thromboprophylaxis